Estudo cintilográfico da circulação esplênica em ratos - Fabio Gontijo Rodrigues (2013)
The blood flow of the human spleen is 350 liters per day. The splenic microcirculation and the dynamics of cell movement within this organ are not completely understood. The closed circulation within the arterioles, capillaries and venules is responsible for less than 10 % of blood flow inside the splenic parenchyma. In the open circulation, most of the blood flows through the perivascular space inside the red pulp of the splenic parenchyma. The aim of this study was to evaluate the vasculoparenchymal blood circulation of the spleen by means of scintigraphic study in rats. Thirty Wistar rats were randomly distributed into six goups (n=5). Group 1 (spleen 30 minutes) and Group 2 (spleen 90 minutes): the rats were laparotomised and the aorta was ligated right above the iliac vessels, the splanchnic arteries were ligated as well, in order to direct the blood flow to the spleen. Group 3 (spleen and stomach 30 minutes) and Group 4 (spleen and stomach 90 minutes): the rats were laparotomised and the aorta was ligated right above the iliac vessels, the splanchnic arteries were ligated as well, preserving the blood flow by splenic and gastric arteries and splenogastric vessels. Group 5 (control 30 minutes) and Group 6 (control 90 minutes): the rats were laparotomised and the aorta was ligated near the iliac vessels. Maintaining the blood flow to the abdominal organs. After ligating these vessels, the animals were submitted to injection of 0.2 ml of sodium pertechnetate in the aorta. The animals were observed for 30 or 90 minutes according to the group they belonged. Scintigraphic images were made in a gama camera. At the end of the following period, the animals have had the spleen removed for radiation counting in an automatic counter. There was no difference in the splenic radiation counts between these groups, showing that there is a retention of the radioisotope in the spleen, even after 90 minutes. In conclusion, the splenic blood flow is not continuos. The blood flows into the splenic parenchyma and its drainage is slow, not following in a predictable sequence.